Analisis dan Perancangan Sistem Kompensasi Berbasis Job Value Pada PT Banjarnegara Agro Mandiri Sejahtera: Analysis and Design of a Job Value Based Compensation System at PT Banjarnegara Agro Mandiri Sejahtera - Rudi Triyono; Furqon Syarief Hidayatulloh (School of Business, Bogor Agricultural University (SB-IPB), 2024)
Background: Banjarnegara Agro Mandiri Sejahtera Ltd is one of the SMEs located in Banjarnegara Regency which is engaged in the food and beverage (fnb) sector. PT Banjarnegara Agro Mandiri Sejahtera has not paid wages in accordance with the applicable minimum wage and has not applied the principle of internal justicePurpose: The purpose of this study is to identify the compensation system implemented by the company, analyze the basic factors in determining the compensation system, and provide recommendations for the ideal compensation design system. Design/methodology/approach: The methods of this research are descriptive analysis, point method, job grading, salary mapping, and adjustments. Findings/Result: Based on the research results, it is known that the ideal compensation system to be implemented by companies is an overlapping compensation system.Conclusion: The ideal compensation system to be implemented by companies is an overlapping compensation system.Originality/value (State of the art): The use of ten compensation factors at PT Banjarnegara Agro Mandiri Sejahtera is based on the company's needs. The overlapping method used is considered more efficient because it minimizes company costs. Keywords: compensation, food and beverage, job value, salary, SMES